(untitled) (Bangladesh Journal of Otorhinolaryngology, 2010)
Metastatic neck node is not uncommon in the otolaryngology department of a tertiary level hospital. Ignorance, illiteracy, delay in seeking medical advice and poor orientation of our general practitioners regarding management causes these patients to suffer from marked morbidity and mortality. It is a prospective study with random selection of sixty (60) cases of metastatic neck node admitted in the otolaryngology department of BSMMU and Dhaka Medical College Hospital during a period extending from September, 2002 to August, 2003. Here 53(88.33%) cases of metastatic neck nodes having a known primary in the head neck region and in other seven (11.67%) cases primary site of malignancy could not be detected. The commonest site of known primary was supraglottic larynx. Highest number 19 (31.67%) of presentation was seen in 5th decade. Male incidence 47 (78.33%) was more compared to female 13 (21.67%). Keywords: Neck gland, Metastatic neck node, Unknown primary. DOI: 10.3329/bjo.v15i1.4307 Bangladesh J of Otorhinolaryngology 2009; 15(1): 26-30